Quantitative Analysis of Macro Foam Integration in Non Pressurized Manned Submersibles (NPMS): A Comprehensive Study of Buoyancy Management and Operational Performance - Ahlan Zulfakhri; Achmad Baidowi; Sunarsih Sunarsih (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2026)
Non-pressurized manned submersibles continue to struggle with fundamental limitations in buoyancy control and energy management, while traditional ballast systems present considerable challenges when operational demands increase, making macro foam technology an intriguing alternative that could address these persistent issues through passive buoyancy enhancement. This study quantitatively evaluates the impact of macro foam integration on NPMS operational parameters by comparing configurations with and without macro foam across multiple performance metrics using actual technical specifications through comprehensive computational analysis examining vehicle mass, buoyancy characteristics, ballast tank specifications, and operational efficiency across four distinct ballast configurations (neutral, forward full, center full, aft full), with performance metrics evaluated using standardized naval engineering protocols based on actual submersible design data. Macro foam integration demonstrated significant improvements across all measured parameters, with tank volume requirements decreasing by 64.4% (from 1466.43L to 521.53L), buoyancy deficit decreasing by 60.7% (from 1.35 to 0.53 tons), total buoyancy increasing by 175% (from 0.65 to 1.79 tons), and ballast requirements reducing by 43.6-60.7% across all configurations, while safety margins improved dramatically with a 3.4:1 emergency buoyancy ratio compared to 0.5:1 without foam. These findings demonstrate that macro foam integration provides fundamental improvements in NPMS operational capability, safety margins, and energy efficiency, with the technology transitioning from optional enhancement to essential operational requirement for practical submersible deployment in modern naval operations.